LEARNING OF REACTION RATE WITH NESTED CURRICULAR ARRANGEMENT TO IMPROVE CRITICAL THINKING SKILLS AND UNDERSTANDING THE CONCEPT OF STUDENTS IN ACTIVE-REFLECTIVE LEARNING - Omes, Maria Fransiska (Universitas Negeri Surabaya, 2019)
This study aims to evaluate the learning rate of reactions by nested curricular arrangement. This learning is designed using the inquiry model. The learning process was attended by 34 XI MIA 7 students of SMAN 1 Manyar, Gresik, East Java. The objects in this study are critical thinking skills and students' understanding of the concept of active-reflective learning styles. This study was designed using